In Vitro Studies of Squalene‐Gusperimus Nanoparticles in Islet‐Containing Alginate Microcapsules to Regulate the Immune Response in the Immediate Posttransplant Period. Issue 11 (5th August 2021) - Navarro Chica, Carlos E.; Qin, Tian; de Haan, Bart J.; Faas, Marijke M.; Smink, Alexandra M.; Sierra, Ligia; López, Betty L.; de Vos, Paul
Abstract : Grafting of microencapsulated pancreatic islets has been proposed as an alternative to exogenous insulin for the treatment of type 1 diabetes mellitus. Microencapsulated islets are protected from direct contact with immune cells and larger immune‐active molecules such as immunoglobulins. Unfortunately, many islet cells in the microcapsules are lost in the immediate period after transplantation due to an early host immune response limiting long‐term function of the graft. Gusperimus has shown to reduce the inflammatory responses to grafted encapsulated islets, but it cannot be appropriately used because it is easily hydrolyzed leading to loss of activity. To temporarily modulate the inflammatory response directly after implantation and stabilize gusperimus, squalene‐gusperimus nanoparticles (Sq‐GusNPs) are developed and incorporated in human islets‐containing alginate‐based microcapsules. A prolonged and continuous release of gusperimus is achieved. This offers an anti‐inflammatory microenvironment in the vicinity of the microcapsules and a reduction of cytokine secretion by lipopolysaccharides‐activated human macrophages. Release of gusperimus from Sq‐GusNPs does not affect the in vitro viability or function of human pancreatic islets. The data illustrate that incorporation of Sq‐GusNPs in alginate microcapsules offers an opportunity to temporarily modulate the immediate immune response after the grafting procedure of encapsulated islets cells and reduce loss of islet cells. Abstract : Incorporation of squalene‐gusperimus nanoparticles in alginate microcapsules allows a controlled and prolonged release of gusperimus. These nanoparticles proportionate an anti‐inflammatory microenvironment in the vicinity of the microcapsules and to the encapsulated islets without affecting their viability or function.